Provocations for Reimagining Informatics Approaches to Health Equity - Valdez, Rupa S.; Ancker, Jessica S.; Veinot, Tiffany C. (Yearbook of Medical Informatics, 2022)
As the informatics community commits to the goal of advancing health equity, it is essential that we openly critique our current approaches and reimagine the ways in which we design, implement, evaluate, and advocate for policies related to informatics interventions. In this paper, we present five provocations as a starting point for building more conscientious informatics practice in service of this goal: 1) Health informatics interventions can create an “illusion of impactful action” without significant material benefits for marginalized patients, families, and communities; 2) Health informatics interventions target the wrong stakeholders, the wrong processes, and the wrong technologies to achieve equity; 3) Informaticians must conceptualize health literacy and other factors shaping patients' experiences as a system-level rather than individual-level characteristic; 4) Informatics interventions wrongly assume that interacting contextual factors can be meaningfully captured by over-simplified structured variables; and 5) Informatics interventions often specify the wrong system boundaries and solution space. We further assert that drastic shifts in our current practices will allow us to honor our claims of valuing patient-centered approaches, especially for marginalized communities.
Keywords: Health disparity; health equity; health informatics; social determinants of health; community engagement